Study on the Application of a Photocatalytic Titanium Dioxide Coating on Glass Beads for the Treatment of Perfluorooctane Sulfonic Acid - Dao Duy Nam; Cao Thi Hong Hanh; Nghiem Minh Huyen; Dieu-Anh Van; Ha Vinh Hung; Vu Minh Trang; Vu Quang Minh; Nguyen Bich Ngoc; Vu Thi Thu Ha; Huynh Trung Hai (Journal of Chemistry)
Perfluorooctanesulfonic (PFOS) acid is a persistent anthropogenic organic fluorinated compound ubiquitous in industrial applications and is resistant to conventional wastewater treatment methods. Human exposure to PFOS can cause adverse health effects. In this study, a low-content titanium dioxide (TiO2) photocatalyst coated on glass beads was synthesized through a simple method and showed improved activity and durability. This material exhibited easy recovery and potential for large-scale applications. The efficacy of the TiO2 nanoparticle-deposited glass beads’ (TiO2@GBs) photocatalyst in treating PFOS contaminants in wastewater was explored, demonstrating its ability to promote photocatalytic reactions to break down PFOS into shorter chain byproducts. The study employed the response surface method (RSM) using the Box–Behnken design (BBD) to optimize treatment conditions at a PFOS concentration of 0.1 mg/L. Investigated factors included pH (4–9), TiO2 dosage (0.11–0.53 g/L), and irradiation time (4–8 h). Design-Expert 12 software was used to plan and optimize the experiments. Fifteen experiments were conducted, and triplicate runs occurred at the center points of the experimental plan. ANOVA and Fisher’s test yielded an F value of 73.88 (p<0.0001) which demonstrated the model’s statistical significance with over 99% confidence regression prediction. The optimized treatment conditions that achieved 100% degradation of PFOS included a pH of 4.55, TiO2 dosage of 0.396 mg/L, and irradiation time of 6.59 hours. After the photocatalytic treatment, PFOS was transformed into intermediate products such as PFPeA, PFHpA, L-PFBS, and L-PFHxS.